Strength and power assessment - Abernethy, P.; Wilson, G.; Logan, P. (Sports Medicine, 1995)
Highlightening a research review paper concerning the assessment of strength and power in sports. It has been abstracted, interpreted, and presented as a summary of the status of this field. Unfortunately, its conclusion is not very positive. It emphasizes that coaches should be wary of promises of value from those who advocate strength and power testing without the appropriate scientific validation and evaluation of protocols. This review article considers the factors associated with strength and power testing. It highlights shortcomings and problems associated with this form of assessment. An underlying theme that is verified by its exhaustive review is that much strength and power testing is invalid and unreliable. The reasons for this status are primarily a failure to scientifically develop testing protocols and validities and then to cross-validate the utility of tests with each sport and level of participant. -purposes of strength and power assessment - three modes of dynamometry: 1. Isometric dynamometry 2. Isoinertial dynamometry 3. Isokinetic dynamometry - Factors which modify strength and power test results - Correlations between test measures and athletic performance - Discriminations between groups of individuals - Sensitivity of testing to training effect - Assumptions of strength and power assessment